2022
DOI: 10.7150/jca.70730
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic Variants of Long Noncoding RNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 on Uterine Cervical Cancer

Abstract: Genetic variants of long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1 (lncRNA MALAT1) have been reported to be associated with several cancers. Until now, no study reveals the associations between lncRNA MALAT1 polymorphisms and cervical cancer (CC). The objectives of this study were to explore the correlations among MALAT1 polymorphisms and occurrence and clinicopathological parameters of CC, as well as patient 5 years survival in Taiwanese women. The study recruited 116 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Finally, we pooled the data of 59 SNPs from 11 different LncRNAs in 21 case-control studies (19 English and 2 Chinese publications) (Guo et al, 2015;Guo et al, 2016;Han et al, 2016;Jin et al, 2016;Qiu et al, 2016;Wu et al, 2016;He and Wei, 2017;Jin et al, 2017;Zhu et al, 2017;Wang and Luo, 2018;Weng et al, 2018;Huang et al, 2019;Jia et al, 2019;Gao et al, 2020;Minn et al, 2020;Wang et al, 2020;Weng et al, 2020;Sun et al, 2022;Yao et al, 2022;Yi et al, 2022). Details of these studies and the distribution of SNPs genotype are shown in Supplementary Table S1.…”
Section: Results Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we pooled the data of 59 SNPs from 11 different LncRNAs in 21 case-control studies (19 English and 2 Chinese publications) (Guo et al, 2015;Guo et al, 2016;Han et al, 2016;Jin et al, 2016;Qiu et al, 2016;Wu et al, 2016;He and Wei, 2017;Jin et al, 2017;Zhu et al, 2017;Wang and Luo, 2018;Weng et al, 2018;Huang et al, 2019;Jia et al, 2019;Gao et al, 2020;Minn et al, 2020;Wang et al, 2020;Weng et al, 2020;Sun et al, 2022;Yao et al, 2022;Yi et al, 2022). Details of these studies and the distribution of SNPs genotype are shown in Supplementary Table S1.…”
Section: Results Characteristics Of Studiesmentioning
confidence: 99%
“…Then, 12 articles were excluded, including 10 articles for which genotype data were not available, 1 article for which the abstract was available, and 1 article for which the full text was not available ( Figure 1 ). Finally, we pooled the data of 59 SNPs from 11 different LncRNAs in 21 case-control studies (19 English and 2 Chinese publications) ( Guo et al, 2015 ; Guo et al, 2016 ; Han et al, 2016 ; Jin et al, 2016 ; Qiu et al, 2016 ; Wu et al, 2016 ; He and Wei, 2017 ; Jin et al, 2017 ; Zhu et al, 2017 ; Wang et al, 2018 ; Wang and Luo, 2018 ; Weng et al, 2018 ; Huang et al, 2019 ; Jia et al, 2019 ; Gao et al, 2020 ; Minn et al, 2020 ; Wang et al, 2020 ; Weng et al, 2020 ; Sun et al, 2022 ; Yao et al, 2022 ; Yi et al, 2022 ). Details of these studies and the distribution of SNPs genotype are shown in Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with ovarian cancer, high levels of MALAT1 expression in localized lesions or in serum exosomes may indicate a poor prognosis ( Lin et al, 2018 ; Qiu et al, 2018 ). However, a study conducted in Taiwan showed that lncRNA MALAT1 gene variants are not associated with the incidence, clinicopathological characteristics, or the 5-year survival rates of women with cervical cancer ( Sun YH. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that genetic variations, such as those prevalent universally present in lncRNA genes, may directly or indirectly affect lncRNA expression levels in multiple ways to regulate tumor development [ 27 , 28 ]. Previous studies have reported that the MALAT1 polymorphisms were associated with cancer development, carcinogenesis and prognosis in various cancers such as hepatocellular carcinoma [ 29 ], cervical cancer [ 30 ], oral squamous cell carcinoma [ 31 ], and prostate cancer [ 32 ]. However, only a small number of researches have looked into the connection between MALAT1 SNPs and lung cancer [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%